Bird Community Structure Reflecting the Health of Wetland; Evidence from Maharana Pratap Wetland, Richha, Faridpur, Northern India - AMIT KUMAR SINGH; SANDEEP K. RAGHUVANSHI; RAJENDRA SINGH (The Bioscan, 2026)
Wetlands are important habitats for the water birds, generally used for food, breeding, nesting and foraging. Water birds are good indicators of ecosystem health. The present study was conducted from October 2024 to September 2025 in Maharana Pratap Wetland, Riccha, Faridpur Range, District Bareilly, Uttar Pradesh, India. During the study period, a total of 38 bird species were found, of which most of the species were under the IUCN category of Least Concern. The Asian woolly-necked stork (Ciconia episcopus) and Oriental Darter (Anhinga melanogaster) belong to the near-threatened category, highlighting the importance of wetlands and their conservation value. Numerous winter visitors were also seen during the study, demonstrating the availability of food and habitat quality of the wetland. Diversity was higher in winter and post-monsoon but found lower during summers, indicating habitat stability. The presence of resident species throughout the year indicates habitat integrity. The Shannon-Wiener diversity index is high in winter and post-monsoon and lower in summer, reflecting the water availability and resource condition. The study provides the measures of the ecological importance of Maharana Pratap Wetland as a year-round habitat for the different bird populations, emphasizing the continued monitoring and conservation of the habitat. Keywords Avifaunal diversity; Wetland birds; Seasonal variation; Shannon–Wiener index; Maharana Pratap Wetland.